2013
DOI: 10.1523/jneurosci.4568-12.2013
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Subtypes Are Specified by the Level ofneurodExpression in the Zebrafish Lateral Line

Abstract: During neural development, even in seemingly homogeneous cell populations, individual neurons acquire diverse morphology and behavior, and even adjacent neurons can establish synaptic connections with distinct targets. Although diversity among individual neurons is essential for a functional nervous system, the underlying molecular mechanism of establishing heterogeneity in a population of neuronal precursors has been poorly addressed at the single-cell level. We focused on the development of the zebrafish pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
1
11
0
1
Order By: Relevance
“…Specifically, elevated Neurod expression increases the number of glucagon-expressing cells but decreases the number of insulin-expressing cells. A similar role has recently been reported for differential levels of Neurod within the developing zebrafish posterior lateral line (PLL) (Sato and Takeda, 2013). In this group of migrating neurons there are two classes of cells, leaders and followers, which express high and low levels of Neurod protein, respectively.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Specifically, elevated Neurod expression increases the number of glucagon-expressing cells but decreases the number of insulin-expressing cells. A similar role has recently been reported for differential levels of Neurod within the developing zebrafish posterior lateral line (PLL) (Sato and Takeda, 2013). In this group of migrating neurons there are two classes of cells, leaders and followers, which express high and low levels of Neurod protein, respectively.…”
Section: Discussionsupporting
confidence: 78%
“…In this group of migrating neurons there are two classes of cells, leaders and followers, which express high and low levels of Neurod protein, respectively. Overexpression of Neurod in a single PLL neuron precursor is sufficient to promote its differentiation into the leader cell type (Sato and Takeda, 2013). Our immunohistochemistry has shown that the individual cells of the dorsal endocrine pancreatic bud similarly display heterogeneous Neurod protein levels (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Neurod1 gene is specifically expressed during central nervous system development in zebrafish and is a key differentiation factor during neurogenesis; it is also involved in the determination of neural subtypes in the ganglia24. At 48 hpf the expression of neurod1 is more specifically localized at tegmentum, diencephalon, hindbrain and lateral line gaglia2526. The vast majority of coasy morphants (85%, n = 45/53) showed altered neurod1 expression.…”
Section: Resultsmentioning
confidence: 99%
“…The afferent neurons of the pLL ganglion are heterogeneous and have been classified into at least two types. The leader neurons (or type A) are the first to differentiate, are characterized by a large soma and are distributed throughout the entire ganglion [ 27 , 43 , 46 ]. The peripheral axonal projections of these neurons comigrate with the primordium and innervate the primary neuromasts [ 43 , 45 ].…”
Section: Introductionmentioning
confidence: 99%